2011
DOI: 10.1037/a0023437
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of listwide control, item-based control, and working memory capacity on Stroop performance.

Abstract: Hypothesized top-down and bottom-up mechanisms of control within conflict-rich environments were examined by presenting participants with a Stroop task in which specific words were usually presented in either congruent or incongruent colors. Incongruent colors were either frequently (high contingency) or infrequently (low contingency) paired with the word. These items were embedded within lists consisting of either 100% congruent or 100% incongruent filler items to create mostly congruent or mostly incongruent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
288
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(339 citation statements)
references
References 42 publications
38
288
12
1
Order By: Relevance
“…In other words, temporal learning QUESTIONING CONFLICT ADAPTATION 15 represents a powerful confound that will contaminate list-level PC experiments and produce a list-level effect even for contingency-unbiased items. Indeed, forthcoming work by Schmidt (2012b) demonstrates the same effect of previous response times on the list-level PC effect in Hutchison's (2011) data. Thus, the list-level PC effect, like the ISPC effect, is explainable in terms of simple learning biases.…”
Section: List-level Proportion Congruentmentioning
confidence: 68%
See 2 more Smart Citations
“…In other words, temporal learning QUESTIONING CONFLICT ADAPTATION 15 represents a powerful confound that will contaminate list-level PC experiments and produce a list-level effect even for contingency-unbiased items. Indeed, forthcoming work by Schmidt (2012b) demonstrates the same effect of previous response times on the list-level PC effect in Hutchison's (2011) data. Thus, the list-level PC effect, like the ISPC effect, is explainable in terms of simple learning biases.…”
Section: List-level Proportion Congruentmentioning
confidence: 68%
“…In most cases, evidence for list-level PC effects independent of ISPC effects was not found (e.g., Blais & Bunge, 2010). There are a few findings, however, that suggest a very small contribution of list-level PC might exist Bugg, McDaniel, Scullin, & Braver, 2011;Hutchison, 2011). For instance, Hutchison compared items of equal item PC that were mixed together with other context items that were either mostly congruent or mostly incongruent.…”
Section: List-level Proportion Congruentmentioning
confidence: 99%
See 1 more Smart Citation
“…A difference between these two conditions can only be attributable to contingency learning. Hutchison (2011) recently performed a similar test in verbal Stroop data, where a contingency learning contribution was also confirmed. 2 Experiment 1 also tested for a contribution of the item-level PC of the word (i.e., low/low vs. low/high).…”
Section: Discussionmentioning
confidence: 82%
“…Recent work has indicated that list-level proportion congruent effects are also observable (e.g., Hutchison, 2011). That is, after accounting for item-specific learning, participants are responsive to the proportion of congruent trials in the task as a whole.…”
Section: Discussionmentioning
confidence: 99%